The Mediating Effect of Organizational Culture on Charismatic Leadership and Corporate Reputation in Banten Regionally Owned Enterprises - Suhartini (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Organizational leadership and culture play a critical role in shaping how organizations are perceived by the public and key stakeholders. This study examines whether organizational culture mediates the relationship between charismatic leadership and corporate reputation. Using a quantitative approach, data were collected through a questionnaire survey employing a five-point Likert scale and analyzed using mediation analysis and structural equation modeling to examine both direct and indirect relationships among the variables. The findings reveal that charismatic leadership positively influences corporate reputation and organizational culture, while organizational culture also exerts a positive effect on corporate reputation. Furthermore, organizational culture partially mediates the relationship between charismatic leadership and corporate reputation, indicating that a strong and supportive culture enhances the effectiveness of charismatic leadership in building a positive organizational image. These results suggest that organizations should integrate leadership development initiatives with cultural strengthening strategies to improve their reputation and sustain stakeholder trust. Therefore, managers should focus not only on developing charismatic leaders but also on cultivating a culture that aligns with organizational values to maximize reputational outcomes.